Relevance of Bioassay of Biologically Active Substances (BAS) with Geroprotective Properties in the Model of the Nematode Caenorhabditis Elegans in In Vivo Experiments - Dyshlyuk, Lyubov S.; Dmitrieva, Anastasiya I.; Drozdova, Margarita Yu.; Milentyeva, Irina S.; Prosekov, Alexander Yu. (Current Aging Science, 2022)
Aging is an inevitable process of nature. The age of living organisms contributes to the appearance of chronic diseases, which not only reduce the quality of life but also significantly damage it. Modern medicines can successfully fight multiple diseases and prolong life. At the same time, medications have a large number of side effects. New research indicates that bioactive phytochemicals have great potential for treating even the most severe diseases and can become an alternative to medicines. Despite many studies in this area, the effects of many plant ingredients on living organisms are poorly understood. Analysis of the mechanisms through which herbal preparations influence the aging process helps to select the right active substances and determine the optimal doses to obtain the maximum positive effect. It is preferable to check the effectiveness of plant extracts and biologically active components with geroprotective properties in vivo. For these purposes, live model systems, such as Rattusrattus, Musmusculus, Drosophila melanogaster, and Caenorhabditis elegans are used. These models help to comprehensively study the impact of the developed new drugs on the aging process. The model organism C. elegans is gaining increasing popularity in these studies because of its many advantages. This review article discusses the advantages of the nematode C. elegans as a model organism for studying the processes associated with aging. The influence of various BAS and plant extracts on the increase in the life span of the nematode, its stress resistance, and other markers of aging is also considered. The review shows that the nematode C.elegans has a number of advantages over other organisms and is a promising model system for studying the geroprotective properties of BAS.
Keywords: neurodegenerative diseases